Disciplinary Intuitions and the Design of Learning Environments - Lim, Kenneth Y. T (Springer, 2016)
Many of the chapters within draw frequent and explicit linkages to curriculum design, from the premise of the need to go beyond addressing the conceptions of learners, to seeking to understand the substrate upon which these conceptions are founded. The argument is made that this substrate comprises the particular set of lived experiences of each learner, and how – because these lived experiences are as tacit as they are diverse – designing curriculum around misconceptions and preconceptions alone would not lead to enduring understanding from first principles. From this perspective, Disciplinary Intuitions constitute an exciting field at the nexus of learning theories and curriculum design.